Onboarding for Pathology Residency Programs—The Montefiore Experience - Tiffany Michele Hébert MD; James Szymanski MD; Jose Mantilla MD; Lauren McLemore DO, MPH; Ronald Walsh MD; Ljiljana Vasovic MD; Jacob J. Steinberg MD; Michael B. Prystowsky MD, PhD (Academic Pathology, 2016)
Onboarding is a system frequently used in the corporate world as a means of orienting incoming employees to their duties and inculcating the workplace values. The program aims to facilitate transition into new work roles and improve employee retention rates. At Montefiore, we have instituted an onboarding curriculum that is given to new anatomic and clinical pathology residents about a month prior to the start of residency. The program includes an introductory video series of basic histology and a series of anatomic and clinical case studies illustrating basic laboratory principles. This didactic content is tagged to learning objectives and short self-assessment modules. In addition, content related to the work ethos at Montefiore and the role of the core competencies and milestones in residency education are included. Finally, a broader component of the onboarding gives the incoming residents a social welcome to our area, including key information about living in the area surrounding Montefiore. The program has been well received by our residents for whom the content has helped to boost confidence when starting. We feel that the program is helpful in ensuring that all incoming residents start having received the same baseline didactic content. Transmitting this didactic content via onboarding allows our residents to begin the work of learning pathology immediately, rather than spending the first weeks of residency covering remedial content such as basic histology. Such a program may be useful to other pathology residencies, most of whom have residents from a range of backgrounds and whose prior exposure to pathology may be limited.